The Sand country of Aldo Leopold : a photographic interpretation - Steinhacker, Charles; Flader, Susan; Leopold, Aldo, 1868-1948 (San Francisco : Sierra Club, 1973)
Those who have come through Leopold's work to share his lucid appreciation of life's essential elegance will find the style of this volume faithful to its inspiration. For those who have heretofore had to infer Leopold's landscape from his prose,the photographs of Charles Steinhacker, who conceived the idea for this book, offer a unique opportunity to see the context from which Leopold's words take their original impetus and meaning. Susan Flader, devoted archivist and student of Leopold's life and work, describes his sand county experience in the larger setting of the area's history and Leopold's own life. And from Aldo Leopold himself, this volume includes a quintessential selection from A Sand County Almanac: and Sketches Here and There." -- Introduction
Keywords: Leopold, Aldo, -- 1868-1948.